Assessing the effects of metal mining effluents on freshwater ecosystems using biofilm as an ecological indicator: Comparison between nanofiltration and nanofiltration with electrocoagulation treatment technologies - Darren Oatley-Radcliffe (Ecological Indicators, 2020)
Abandoned mines cause serious environmental damage to their surroundings with considerable impacts on freshwater ecosystems. These impacts occur mainly due to the uncontrolled discharge of polluted effluents, which may contain high concentrations of heavy metals. Currently, no real solution exists for this important environmental problem, leaving a legacy of global pollution. This study aimed to assess the impact of a metal mining effluent from an abandoned mine on freshwater ecosystems, using aquatic biofilms as an ecological indicator. At the same time, the efficiency of different innovative treatment technologies in reducing the ecological impacts caused by mining effluents was evaluated, consisting of nanofiltration and nanofiltration combined with electrocoagulation. To do that, aquatic biofilms obtained from a pristine stream, were exposed, under microcosms conditions, to a metal mining effluent, untreated or treated by the innovative treatment technologies and responses were compared with unexposed biofilm which served as control. The structural and functional responses of the biofilm were measured with throughout time. Biofilms that were exposed to the untreated mining effluent showed significant differences respect to the rest of treatments and the control, particularly exhibiting inhibitory effects on photosynthetic efficiency just after 24 h of exposure and a progressive shift of the photosynthetic community composition throughout the exposure period. The treatment technologies significantly reduced the ecological impact caused by the metal mining effluent. However, metal bioaccumulation in biofilm revealed a potential long-term impact. These observations evidenced the biofilm as a useful ecological indicator to assess the ecological impact caused by metal mining effluents on freshwaters and the efficiency of different treatment technologies to reduce it.